Experimental Study to Improve the Castability of Aluminum Killed Cold Heading Steel. Issue 8 (18th February 2013) - Jun, Yang; Bo‐Tao, Chen; Wei, Tang; Fan‐Zheng, Zeng; Gang, Yu; Feng, Shen
Abstract Experimental study on the LF refining of aluminum killed cold heading steel shows that calcium content in the molten steel increased to about 0.0010% at the end of refining, and the aluminum deoxized products were transformed from Al2O3 to the complex inclusions CaO–MgO–Al2O3 with lower melting point by the high basicity, high Al2O3, and strong deoxidizing slag. The inclusions are in liquid state and can be easily floated up during LF refining and continuous casting. The total oxygen content of the steel falls to about 0.0020%. The experimental technology uses only 50 m calcium wire to the 80‐t heat or even without calcium treatment. As compared to the traditional technology with higher amount of calcium for treatment, which forms CaS and CaO–MgO–Al2O3 inclusions with high melting point, the experimental technology improves the castability and reduces the manufacturing cost.